The impact of Blended Learning in Teaching and Learning during the COVID-19 - NISANA, FATHIMA (2021)
The purpose of this study was to find out the impact of blended learning in teaching and learning in the light of COVID-19 in a private school in the UAE. The study was carried out to investigate critically, the usefulness of blended learning in the continuation of education and its effectiveness. A mixed-method approach was used for data collection. Data was collected through surveys and interviews. 72 participants took part in the study. Students, teachers, and parents expressed their views on blended learning. To calculate the mean and standard deviation of quantitative data Microsoft Excel was used and thematic analysis was used for qualitative data. The researcher found out that the instructors, learners, and parents had a positive approach to blended learning. The efficacy of blended learning was calculated through factors such as feedback, collaboration, motivation, and assessment. However, participants suggested that proper training should be given in terms of technology adoption.